PENGEMBANGAN MEDIA PEMBELAJARAN BUKU CERITA BERGAMBAR UNTUK PEMBELAJARAN MENULIS KALIMAT SEDERHANA SISWA KELAS II SEKOLAH DASAR - Putri Ismaya; Petrus Paulus Mbette Suhendro; Iva Sarifah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT The research aims to develop a Picture Storybook learning medium for teaching simple sentence writing to second grade elementary school students. This research is a development study using the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The data in this study were obtained through interviews, observations, and questionnaires. The validation results from the media expert showed feasibility with a percentage of 98,3%, from the material expert 95%, and from the language expert 90%. The average validation score from all experts was categorized as very good. The trial results by students showed a one-to-one test result of 96,6%, a small group test of 99%, and a field test of 92,5%. The average result from all student trials was categorized as very good. Thus, it can be concluded that the developed Picture Storybook learning medium can be used as a learning medium for writing simple sentences with sentence elements of subject (S), predicate (P), and object (O) in the second grade of elementary school. Keywords: Picture Storybook, Simple Sentences, Writing Beginnings.